Regularized lattice Bhatnagar–Gross–Krook model for the thermal flow in porous media. (February 2018) - Wang, Zuo; Zhang, Jiazhong; Liu, Yan; Wang, Le
A regularized lattice Bhatnagar–Gross–Krook model for flow and heat transfer in porous media at the representative element volume scale is presented. In the model, the regularization process is extended to the existing Darcy–Forchheimer-based lattice Bhatnagar–Gross–Krook scheme. Numerical results show good agreement between the present model and the previous ones. Also, the present model shows better numerical stability than its lattice Bhatnagar–Gross–Krook counterpart.